Research on Information Literacy Education of University Libraries under MOOC Environment - *, jyx; Ding, Yi; Jin, Mengqi (IJRDO- Journal of Educational Research, 2018)
MOOC is a brand-new education mode with rapid development in recent years, and information literacy has become an indispensable basic ability in the era of big data. MOOC brings opportunities and challenges to the cultivation of information literacy in University libraries. Based on the analysis of the relationship between MOOC and information literacy education in University libraries, this paper constructs an information literacy education model of University Libraries under MOOC environment, and puts forward some countermeasures and suggestions for improving information literacy education in University libraries.